Digital gangrene in spinal tuberculosis - Hussain, Masaraf; Sharma, Shriram; Synmon, Baia; Hynniewta, Yasmeen (Indian Journal of Case Reports, 2020)
Though tuberculosis (TB) is commonly seen, peripheral gangrene as a manifestation of TB is not common. Spinal TB presents with backache, paraparesis, or quadriparesis with or without bladder and bowel involvement. It may cause spinal deformities. However, peripheral gangrene is not a common manifestation of spinal TB. Here, we present the case of spinal TB, with peripheral gangrene in a 30-year-old female. There was blackening and shrinkage of the left third toe, with superficial tenderness, darkening, and loss of sensation over the left fourth and fifth toes. Tuberculin test and Mantoux test were positive. The magnetic resonance imaging findings were suggestive of Pott’s spine. Arterial Doppler of the affected lower limb revealed sluggish flow, as suggested by the biphasic waveform. The patient was started on antituberculous treatment. Although the neurological symptoms improved with antituberculous treatment, the peripheral gangrene resolved only partially and required amputation.